2015
DOI: 10.7150/jca.11308
|View full text |Cite
|
Sign up to set email alerts
|

Could Somatostatin Enhance the Outcomes of Chemotherapeutic Treatment in SCLC?

Abstract: Purpose: Somatostatin is a peptide with a potent and broad antisecretory action, which makes it an invaluable drug target for the pharmacological management of pituitary adenomas and neuroendocrine tumors. Furthermore, somatostatin (SST) receptors (SSTR1, 2A and B, 3, 4 and 5) belong to the G protein coupled receptor family and are overexpressed in tumors. Since, human small-cell lung cancer overexpresses somatostatin receptors (STTR), they could be legitimate targets for treating SCLC.The aim of this study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The prognosis of SCLC remains extremely poor mainly for recurrence and chemoresistance, but the mechanism of chemoresistance is still unclear 20 . It has been reported that lncRNAs were involved in anticancer drug resistance 19 , 21 – 25 .…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis of SCLC remains extremely poor mainly for recurrence and chemoresistance, but the mechanism of chemoresistance is still unclear 20 . It has been reported that lncRNAs were involved in anticancer drug resistance 19 , 21 – 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Since somatostatin is able to exert antiproliferative effects and reduce tumor growth by suppressing the synthesis and secretion of growth factors, including IgF-1, an important modulator of many neoplasms, 38,39 we measured IgF-1 levels before and after treatment, without nonetheless finding any statistically significant impact on patients’ survival.…”
Section: Discussionmentioning
confidence: 99%
“… 12 Regarding SCLC chemotherapy is still the considered the best first line treatment, however; several novel therapies are being investigated. 13 - 16 The role of tyrosine kinase inhibitors as neo-adjuvant or adjuvant treatment is still under investigation. One observation has to be taken into serious consideration that if chemotherapy is administered in EGFR positive patients as neo-adjuvant treatment then the mutation status will change along with the gene status of several other involved pathways with an unknown treatment effect in the future if treatment will become necessary (disease relapse).…”
Section: Introductionmentioning
confidence: 99%